Comparison of B-Mode with B-Flow Sonography for the Evaluation of Femoral Arteries in Infants - Groth, Michael; Dammann, Elena; Arndt, Florian; Ernst, Marielle; Herrmann, Jochen (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose To evaluate femoral arteries (FAs) in infants in the context of catheter angiography with B-mode (BMS) and B-flow sonography (BFS) and to compare both methods for vessel delineation and reliability of vessel diameter measurements.Methods 21 consecutive infants who underwent ultrasound for the evaluation of FAs before or after cardiac catheterization were retrospectively included in this study. The diameter of the FAs and the maximum length of the vessel section displayed on a single ultrasound plane were recorded by two radiologists for BMS and BFS. The visual image quality was rated by one observer. Statistics included intraclass correlation coefficient, Bland-Altman analysis, Fisher´s exact test and t-test.Results The intraobserver as well as interobserver correlation was excellent for BMS (0.7922 and 0.6521) and BFS (0.8094 and 0.7637). The Bland-Altman analysis revealed limits of agreement for BMS between +/–0.73 mm (intraobserver) and +/–0.55 mm (interobserver) and for BFS between +/–0.83 mm (intraobserver) and +/–0.7 mm (interobserver). BFS allowed visualization of a longer stretch of the FA than BMS (length 3.54 +/–0.85 vs. 2.21 +/–0.9 cm, p < 0.0001). The image quality was significantly higher for BFS (p = 0.0043).Conclusion Since BFS shows excellent reproducibility for vessel measurements and superior image quality in infants, if available, BFS should be included in standard protocols when realistic measurements are required.Key Points Citation Format
Keywords: femoral artery; measurement; ultrasound; B-flow sonography; B-mode sonography